Hak Rasa Aman dalam Perspektif UU No. 39 Tahun 1999 dan Hadis Qudsi Imam Muslim No. 4674 - Farizi, Muhammad Luthfi Al; Arifin, Tajul (Journal of Literature Review, 2025)
Human rights which are the natural rights of humans that come from God, have one important part, namely the right to a sense of security. This right is an important part of human rights; therefore this right is regulated in Law No. 39 of 1999, Article 33. In addition to being regulated in law, the right to a sense of security is also considered important in Islam, this can be seen in the hadith qudsi narrated by Imam Muslim no. 467. Departing from the importance of the right to a sense of security, this study was conducted with the aim of the right to a sense of security in the perspective of positive law and hadith, using the literature study method and information collected from various journal articles then studied with a normative-descriptive approach. The results of this study are the harmony between positive law and hadith in viewing the right to a sense of security, where both positive law and hadith consider that the right to a sense of security is an important right to be maintained and respected by all parties.